Integrative multi-omics analyses identify PKD1 and SLC2A4 as genetically supported glycolysis-related candidate genes for rheumatoid arthritis - A, Xinyu; Xin, Pengfei; Zheng, Lin; Xu, Bo; Wang, Jianye; Sun, Songtao; Xie, Jun; Gao, Chenxin; Pan, Peijun; Qiu, Guowei; Jin, Lang; Shen, Jun; et al. (Frontiers in Immunology, 2026)
IntroductionGlycolytic reprogramming has been implicated in rheumatoid arthritis (RA) pathogenesis, yet the underlying causal genes and epigenetic mechanisms remain unclear. This study aimed to systematically identify glycolysis-related genes and their methylation-regulated expression that may causally influence RA susceptibility.MethodsWe conducted a multi-omics Mendelian randomization (MR) analysis integrating genome-wide association study (GWAS) summary statistics for RA (FinnGen, UK Biobank, GCST90129453) with quantitative trait loci (QTLs) for blood-derived methylation (mQTL), expression (eQTL), and protein abundance (pQTL). Summary-data-based Mendelian randomization (SMR) and colocalization analyses were used to identify causal molecular signatures linking DNA methylation, gene expression, and protein abundance with RA risk. Replication was performed in independent RA cohorts. In addition, qPCR validation was conducted in an independent whole-blood cohort (30 RA patients and 30 healthy controls).ResultsSMR identified 129 CpG sites (75 genes), 28 transcripts, and 9 proteins significantly associated with RA risk. Seven glycolytic genes—PKD1, SLC2A4, ALAS1, ALDH7A1, LRFN3, PFKFB2, and PYGB—showed consistent evidence across methylation, expression, and GWAS datasets. Notably, hypomethylation at cg07036112 (PKD1; OR = 0.68, 95% CI: 0.59–0.78) and cg06891043 (SLC2A4; OR = 0.92, 95% CI: 0.89–0.96) was associated with increased gene expression and increased RA susceptibility. Colocalization supported shared causal variants at these loci (PP.H4 > 0.5). Additional signals included cg13241645 (ALAS1; OR = 0.72, 95% CI: 0.65–0.80) and cg01380361 (PFKFB2; OR = 1.33, 95% CI: 1.17–1.51). qPCR confirmed increased PKD1 and SLC2A4 mRNA expression in RA compared with healthy controls.DiscussionThis integrative multi-omics MR framework supports an epigenetically mediated contribution of glycolysis-related regulation to RA susceptibility and nominates PKD1 and SLC2A4 as robust genetically supported candidate genes. These findings highlight methylation-linked transcriptional changes in glycolysis-related pathways implicated in RA and suggest potential biomarkers and therapeutic targets.